THE PORTRAYAL OF ENGLISH GENTLEMAN IN THE NINETEENTH CENTURY AS SEEN IN DICKENS’ GREAT EXPECTATIONS NOVEL - Muhajir, Fatimah (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
This study deals with the portrayal of English gentleman in the 19th century as seen in Charles Dickens' Great Expectations. The purpose of this study is to describe a portrait of the English gentlemen that are represented by the characters such as Pip, Herbert Pocket, Dumble, Mattew Pocket, Mr. Jaggers and Compeyson as illustrated by Dickens. This research uses descriptive  qualitative method and sociology of literature theory by Diana Lawrenson and Alan Swingewood in analyzing the relationship between the portrayal of English gentelman and its social conditions in at the time. The results of this study  shows that there are several categories of gentelman title that represented by the characters in the story, namely:  Drummle is gentleman by birth (aristocrats), Pip is gentleman by wealth, Gentleman by education or the gentleman students include Pip, Herbert Pocket, and Dummle. The gentleman by profession represented by Mr. Matthew and Mr.Jaggers. While moral code ethics of the gentleman can detemine a man if he the true gentleman or  fake / wicked gentleman. In fact the true gentleman in this story is Mr. Matthew while the fake gentleman is Compeyson.